1723 Conn. Acts 292, An Act for Preventing Lending Guns, Ammunition etc. to the Indians - (:unkn) unknown (General Publisher, 1723)
Prohibited giving or selling “any Indian” guns and ammunition.
--
Keywords: TRANSFER